Niclosamide suppresses cell migration and invasion in enzalutamide resistant prostate cancer cells via Stat3‐AR axis inhibition. Issue 13 (13th May 2015) - Liu, Chengfei; Lou, Wei; Armstrong, Cameron; Zhu, Yezi; Evans, Christopher P; Gao, Allen C.
<x xml:space="preserve">Abstract</x> PURPOSE It is known that over expression of IL6 in prostate cancer cells confer enzalutamide resistance and that this may occur through constitutive Stat3 activation. Additionally, recent pre‐clinical studies suggested enzalutamide might have the potential adverse effect of inducing metastasis of prostate cancer cells via Stat3 activation. This study is aimed to target Stat3 activation and improve enzalutamide therapy. EXPERIMENTAL DESIGN Sensitivity of prostate cancer cells to enzalutamide was tested using cell growth assays and clonogenic assays. Wound healing and invasion assays were performed to determine cell migration and invasion in vitro. Quantitative reverse transcription‐PCR, ELISA and Western blotting were performed to detect expression levels of PSA, c‐Myc, survivin, Stat3, and AR. ChIP assay was performed to examine recruitment of AR to the PSA promoter. RESULTS In the present study, we found niclosamide, a previously identified novel inhibitor of androgen receptor variant (AR‐V7), inhibited Stat3 phosphorylation, and expression of downstream target genes. Niclosamide synergistically reversed enzalutamide resistance in prostate cancer cells and combination treatment of niclosamide with enzalutamide significantly induced cell apoptosis and inhibited cell growth, colony formation, cell migration and invasion. Knock down of Stat3 abrogated enzalutamide resistance resulting in reduced recruitment of AR to the PSA promoter in prostate cancer cells expressing IL6. Moreover, niclosamide reversed enzalutamide resistance by down‐regulating Stat3 target gene expression Stat3and abrogating recruitment of AR to PSA promoter resulting in PSA inhibition. CONCLUSIONS This study demonstrated the IL6‐Stat3‐AR axis in prostate cancer is one of the crucial mechanisms of enzalutamide resistance. Niclosamide has the potential to target the IL6‐Stat3‐AR pathway to overcome enzalutamide resistance and inhibit migration and invasion in advanced prostate cancer. Prostate 75:1341–1353, 2015. © 2015 Wiley Periodicals, Inc.